2023
DOI: 10.3389/fpubh.2023.1247661
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic and other factors associated with unfavorable tuberculosis treatment outcomes—Almaty, Kazakhstan, 2018–2021

Malika Gabdullina,
Edmond F. Maes,
Roberta Z. Horth
et al.

Abstract: IntroductionThe COVID-19 pandemic negatively influenced the availability of tuberculosis (TB) services, such as detection, diagnosis and treatment, around the world, including Kazakhstan. We set out to estimate the COVID-19 pandemic influence on TB treatment outcomes by comparing outcomes among people starting treatment before the pandemic (2018–2019) and during the pandemic (2020–2021) and to determine risk factors associated with unfavorable outcomes.MethodsWe conducted a retrospective cohort study among all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Similar studies also reported that patients who started treatment during the pandemic were 1.85 times (95% CI 1.46 to 2.36) more likely to have poor outcomes than those who started treatment before the pandemic. 47 A study conducted in Turkey found that the proportion of patients who failed treatment during the pandemic increased from 1.9% to 17% (p=0.018). 12 COVID-19 has put enormous pressure on healthcare systems and limited the provision of necessary medical services.…”
Section: Dovepressmentioning
confidence: 99%
“…Similar studies also reported that patients who started treatment during the pandemic were 1.85 times (95% CI 1.46 to 2.36) more likely to have poor outcomes than those who started treatment before the pandemic. 47 A study conducted in Turkey found that the proportion of patients who failed treatment during the pandemic increased from 1.9% to 17% (p=0.018). 12 COVID-19 has put enormous pressure on healthcare systems and limited the provision of necessary medical services.…”
Section: Dovepressmentioning
confidence: 99%